Meningkatkan Hasil Belajar Siswa dengan Menerapkan Metode Diskusi pada Pembelajaran IPAS di Kelas IV SDN Tanjungpakis I - Ade Safitri; Usep Saefuddin (Universitas Muria Kudus, 2025)
This research aims to describe improvements in student learning outcomes through the application of discussion methods in the science and science learning process in class IV. Preliminary observation results show that 60.71% of class IV students at SDN Tanjung Pakis I have learning outcomes below the KKTP. The research method uses Classroom Action Research. Research Procedures were carried out in two cycles, where each cycle included two meetings covering the planning, implementation, observation and reflection stages. The data collection technique was carried out by applying a test instrument in the form of essay test questions. The data analysis technique uses quantitative data, namely calculating the average and pass percentage. The research results showed that the pre-cycle average was 63.92, the first cycle reached 78.57 and the second cycle reached 86.42. There was an increase of 14.65 from pre-cycle to cycle I and 7.85 from cycle I to cycle II or a total increase of 22.5. The student pass percentage was 39.29% in pre-cycle, 78.57% in cycle I and 100% in cycle II. An increase in the pass percentage was found of 39.28% from pre-cycle to cycle I, 21.43% from cycle I to II or a total increase of 60.71%. Thus, the discussion method can improve students’ learning scores in science and science subjects in class IV at SDN Tanjungpakis.